Effect of Nutrient Restriction and Re-Feeding on Calpain Family Genes in Skeletal Muscle of Channel Catfish (Ictalurus punctatus) - Preziosa, Elena (Public Library of Science, 2013)
BACKGROUND: Calpains, a superfamily of intracellular calcium-dependent cysteine proteases, are involved in the cytoskeletal remodeling and wasting of skeletal muscle. Calpains are generated as inactive proenzymes which are activated by N-terminal autolysis induced by calcium-ions. METHODOLOGY/PRINCIPAL FINDINGS: In this study, we characterized the full-length cDNA sequences of three calpain genes, clpn1, clpn2, and clpn3 in channel catfish, and assessed the effect of nutrient restriction and subsequent re-feeding on the expression of these genes in skeletal muscle. The clpn1 cDNA sequence encodes a protein of 704 amino acids, Clpn2 of 696 amino acids, and Clpn3 of 741 amino acids. Phylogenetic analysis of deduced amino acid sequences indicate that catfish Clpn1 and Clpn2 share a sequence similarity of 61%; catfish Clpn1 and Clpn3 of 48%, and Clpn2 and Clpn3 of only 45%. The domain structure architectures of all three calpain genes in channel catfish are similar to those of other vertebrates, further supported by strong bootstrap values during phylogenetic analyses. Starvation of channel catfish (average weight, 15–20 g) for 35 days influenced the expression of clpn1 (2.3-fold decrease, P<0.05), clpn2 (1.3-fold increase, P<0.05), and clpn3 (13.0-fold decrease, P<0.05), whereas the subsequent refeeding did not change the expression of these genes as measured by quantitative real-time PCR analysis. Calpain catalytic activity in channel catfish skeletal muscle showed significant differences only during the starvation period, with a 1.2- and 1.4- fold increase (P<0.01) after 17 and 35 days of starvation, respectively. CONCLUSION/SIGNIFICANCE: We have assessed that fasting and refeeding may provide a suitable experimental model to provide us insight into the role of calpains during fish muscle atrophy and how they respond to changes in nutrient supply.